Venantius Fortunatus as an Aulic Poet: (Carm. 6.1 and 6.5) - Kintli, Dóra (Sapiens ubique civis, 2023)
This paper examines Venantius Fortunatus’s aulic stand in two of his carmens: an epithalamium written for king Sigibert’s wedding with the Visigoth princess Brunchild (Carm. 6.1), and a consolation written for the death of Galswinth, Brunchild’s sister, who married to Sigibert’s brother, and died tragically under suspicious circumstances (Carm. 6.5). Both poems were written for the Austrasian court with a political motivation behind; therefore the question arises, whether Fortunatus could preserve his integrity, and what kind of messages he conveyed through literary allusions and rhetorical tools.